Perancangan UI/UX aplikasi Kabupaten Semarang Virtual Tourism Destination menggunakan metode Goal Directed Design - Handika, Rosalina Dyah; Nugroho, Adi (AITI, 2025)
Semarang Regency is a tourism destination rich in natural beauty, cultural diversity, and fascinating historical heritage. Innovation is needed to optimize the potential of tourism by providing information to tourists. This research applies the Goal Directed Design (GDD) method to design the Semarang Regency Virtual Tourism Destination application called "Tourism Gemspace," which aims to make it easier for tourists to search for destinations and introduce tourism potential. Focusing on application UI/UX design, this research involves six stages of GDD: Research, Modelling, Requirements, Framework, Refinement, and Support. The evaluation results were tested using the System Usability Scale (SUS). An average score of 76.10 was obtained, indicating user satisfaction and satisfactory quality of the UI/UX of the designed application. Overall, the UI/UX of the application was rated as good by respondents with a Grade B, which indicates that the quality of the system design has met user expectations. Thus, this research contributes to presenting an application that meets the needs of modern tourists to explore the tourism potential of Semarang Regency and supports local economic growth and promotion in Semarang Regency.